2014
DOI: 10.1111/bcpt.12342
|View full text |Cite
|
Sign up to set email alerts
|

Mucus as a Barrier to Drug Delivery – Understanding and Mimicking the Barrier Properties

Abstract: Viscoelastic mucus lines all mucosal surfaces of the body and forms a potential barrier to mucosal drug delivery. Mucus is mainly composed of water and mucins; high molecular weight glycoproteins forming an entangled network. Consequently, mucus forms a steric barrier, and due to its negative charge and hydrophobic domains, the overall hydrophilic mucus also presents an interactive barrier limiting the free diffusion of components within and through the mucus. Furthermore, mucus is a dynamic barrier due to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
196
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(196 citation statements)
references
References 49 publications
0
196
0
Order By: Relevance
“…To overcome this biological barrier caused by some novel inhalation pharmaceuticals, functionalized and nontoxic nanocarriers can be used. Inspired from viruses, nanosized particles with neutrally charged coatings such as polyethylene glycol (PEG) can efficiently penetrate the mucus layer in contrast to charged particles (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this biological barrier caused by some novel inhalation pharmaceuticals, functionalized and nontoxic nanocarriers can be used. Inspired from viruses, nanosized particles with neutrally charged coatings such as polyethylene glycol (PEG) can efficiently penetrate the mucus layer in contrast to charged particles (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Mucoadhesion is a complex phenomenon that comprises the humectation of the polymer in contact with the mucus, and also specific interactions between mucoadhesive polymers and mucin. Excellent reviews can be found elsewhere (Boegh & Nielsen, 2015;Alexander, 2011;Harding, 2006;Smart, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The exact composition, thickness and structure of mucus are mainly governed by the nature of the tissue that is being protected, and the amount of salts and other minor components. In the case of gastric mucus, it has been studied that in acid media, mucins change their conformation forming a high viscous gel (Boegh & Nielsen, 2015;Hong et al, 2005). This gel becomes an efficient layer that protects the stomach from being ingested by its own gastric acid during digestion.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of cell-based model in 2D and the lack of dynamic culture environment could explain this observation. The second shortcoming of the mucus produced by cell-based model is its structure and composition [70]. Some differences between mucus from cell culture and native mucus have been highlighted as the mesh spacing [71] or the mucin expression pattern.…”
Section: New Improved Intestinal Barriersmentioning
confidence: 99%